Implementation and Development Models of Character Education in School - Ahmad Muthohar (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2021)
Character education has become an educational policy in Indonesia. It aims to prepare a generation of nations who are superior, advanced, and competitive in the global arena. However, the implementation and development models in schools are different. Each school has a program, strategy, and method for implementing it. This study aims to determine the implementation and development so that the model can be found in schools. The hope is that it will become a means of replication, modification, dissemination, and innovation by other schools. The research was conducted with field research at junior high schools in the city of Samarinda, East Kalimantan with a qualitative descriptive approach. Data collection techniques by observation, interviews, Focus Group Discussion, and documentation. Analysis with critical analysis and content analysis. The results showed: 1) schools have awareness of the importance of character education; 2) there are 5 implementation models in schools, namely integration through curricular, co-curricular, self-development / extra-curricular programs; routine habituation and integration of thematic interconnections between curricular and co-curricular programs; 3) each school has different models in terms of management policies, program quality, priority character values , and implementation strategies.